Merry Christmas, Curious George - Hapka, Cathy; Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Young, Mary O'Keefe. (Boston, Mass. : Houghton Mifflin, 2006)
Separated from the man in the yellow hat while at a Christmas tree farm, Curious George ends up at a hospital where he delights the child patients with his own brand of tree trimming.
Accelerated Reader AR
Keywords: Monkeys -- Fiction; Christmas trees -- Fiction; Medical fiction; Christmas -- Fiction